2013
DOI: 10.1002/sys.21273
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Progress Plans Using a Performance‐Based Expert Judgment Model to Assess Technical Performance and Risk

Abstract: Systems engineers are routinely tasked with facilitating the delicate balance between cost, schedule, and technical performance in acquisition programs that are continuously subjected to various outside influences. While there are several quantitative methods to estimate acquisition program cost and schedule performance as well as identify their risks (e.g., Earned Value Management), the estimation of technical performance and technical risk is generally heuristic in nature. In order to monitor the progress of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…There is a perception that better performing experts can be selected or weighted on the basis of their credentials . We found little evidence to support this contention (Supporting Information 1: Section ).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…There is a perception that better performing experts can be selected or weighted on the basis of their credentials . We found little evidence to support this contention (Supporting Information 1: Section ).…”
Section: Discussionmentioning
confidence: 80%
“…In reliability, judgements used to inform decisions and assessments are often derived by a single expert and may be made heuristically . Our study revealed the serious risk such practices may pose (particularly in terms of overconfidence) and demonstrated that key steps of structured elicitation protocols can improve the final judgements.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations